Non-cooperative game-theoretic distributed power control technique for radar network based on low probability of intercept - Shi, Chenguang; Wang, Fei; Sellathurai, Mathini; Zhou, Jianjiang (IET signal processing, 2018)
Here, the problem of non-cooperative game-theoretic distributed power control is studied in a radar network system based on low probability of intercept (LPI) subject to the signal-to-interference-plus-noise ratio (SINR) constraint and the transmit power constraint of each radar, where all the radars in the network share the same frequency band. The objective is to improve the LPI performance by reducing the transmit power caused by some radars' SINRs over the specified threshold. First, a novel LPI performance-oriented utility function is defined as a metric to evaluate power control. Then, consider that radars in the network are self-interested to maximise their own utilities, the distributed power control problem is formulated as a non-cooperative game, and an iterative power control algorithm is proposed that converges quickly to the Nash equilibrium (NE) of the non-cooperative game. Finally, the existence and uniqueness of NE are proved analytically. Numerical simulation results are provided to demonstrate that, compared with other methods, the presented algorithm not only guarantees the minimum SINR requirements of all radars but also improves the LPI performance for radar network.